2015
DOI: 10.1098/rsta.2014.0223
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry structure in discrete models of biochemical systems: natural subsystems and the weak control hierarchy in a new model of computation driven by interactions

Abstract: Interaction computing is inspired by the observation that cell metabolic/regulatory systems construct order dynamically, through constrained interactions between their components and based on a wide range of possible inputs and environmental conditions. The goals of this work are to (i) identify and understand mathematically the natural subsystems and hierarchical relations in natural systems enabling this and (ii) use the resulting insights to define a new model of computation based on interactions that is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Building on many years of prior work, Nehaniv et al [6] present a mathematical model based on finite automata for diverse biological systems, that can be extended hierarchically to any level of aggregation of constituent parts. They identify the symmetries and the substructures that lead to interesting behaviour and interpret how control and dependencies flow through the network.…”
Section: Models and Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on many years of prior work, Nehaniv et al [6] present a mathematical model based on finite automata for diverse biological systems, that can be extended hierarchically to any level of aggregation of constituent parts. They identify the symmetries and the substructures that lead to interesting behaviour and interpret how control and dependencies flow through the network.…”
Section: Models and Theoriesmentioning
confidence: 99%
“…Among the recurring features of our examples, we note the importance of including transduction between these substrates in any analysis, because extra computation can be hiding in the transduction process. Indeed, in a paper in this issue, Nehaniv et al [6] explicitly model transduction as 'transformers' connecting automata into networks, and their 'transformers' are themselves a special type of automaton. Another aspect common to many of our examples is the incomplete understanding of such systems due to their hybrid nature being little studied as such.…”
mentioning
confidence: 99%
“…While the modeling approach in Egri-Nagy and Nehaniv (2008) is applied on a different level of abstraction (the transformations of a semigroup map molecules onto each other, in contrast to our approach where atoms are mapped), there is an interesting similarity. In Nehaniv et al (2015), local substructures that exhibit symmetry on a network level are found to be permutation groups. Such permutation groups are considered as natural and important subsystems (a ''pool of local reversibility'').…”
Section: Graph Transformation and Semigroups For Labeling 279mentioning
confidence: 99%
“…Such a dynamical system has a higher level meta-dynamics. Approaches such as BIOMICS [8,28] and MGS [12,33] provide suggestive starting points for such languages.…”
Section: How Well Does a Computational Model Fit?mentioning
confidence: 99%